RUMAH SAKIT PARU DENGAN PENDEKATAN HEALING ENVIRONMENT DI KABUPATEN SRAGEN - Rachel Greaty Gracia; Sri Yuliani; Dyah Susilowati Pradnya Paramita (ARSITEKTURA, 2016)
Pulmonary Hospital Design with healing environment approach in Sragen is motivated by the increase in cases of lung disease in Sragen caused by viruses, bacteria, unhealthy lifestyle, and declining air quality. However, Sragen doesn’t have yet a health facility that specialized in pulmonary and respiratory diseases, so the aim of this plan is to create a health facility in Sragen which is form Pulmonary Hospital. Design issue is how to apply the concept of healing environment on the elements of space that can reduce the impact of fear for the patient and landscape arrangement to be one of healing therapy. The method used is architectural design method. Pulmonary Hospital design is the result of the analysis of space requirements, the processing site, the order of mass, mass composition, arrangement of space, and processing landscape by using a healing environment to help the recovery of the patient physically and psychologically.